2013
DOI: 10.1186/1471-244x-13-249
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and quality of life in older persons: relative contributions of fixed and modifiable risk factors

Abstract: BackgroundWith a rapidly ageing population and increasing life expectancy, programs directed at improving the mental health and quality of life (QOL) of older persons are extremely important. This issue may be particularly relevant in the aged-care residential sector, where very high rates of depression and poor QOL are evident. This study aims to investigate the fixed and modifiable risk factors of psychological distress and QOL in a cohort of Australians aged 60 and over living in residential and community s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 62 publications
4
48
0
2
Order By: Relevance
“…In turn experience in the general community (e.g. Atkins et al, 2013) suggests that lower levels of psychological distress among older people are associated with reduced physical, functional and cognitive declines.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In turn experience in the general community (e.g. Atkins et al, 2013) suggests that lower levels of psychological distress among older people are associated with reduced physical, functional and cognitive declines.…”
Section: Discussionmentioning
confidence: 98%
“…For example, exercise is an important activity for promoting well-being among older people in the general community (Atkins, Naismith, Luscombe, & Hickie, 2013). However, the available literature indicates some older prisoners encounter challenges completing exercise due to regime difficulties (e.g.…”
Section: Literature Review Prison Programs and Activitiesmentioning
confidence: 99%
“…A previous study showed, for example, that volunteering improved mental health by enhancing the participants’ range of social networks [38]. Atkins et al reported that lower levels of social support were related to higher psychological distress [40]. Moreover, women, more than men, tend to build relationships from their wide and diverse networks, and women may be inclined to receive positive benefits from community involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Potential reasons may include a greater emphasis on the quality of life over quantity. Poorer functional status was found to predict higher levels of psychological distress and decreased quality of life in this age group [22]. In addition, functional dependency confers greater risk for postoperative complications and risk of discharge to a post-acute care facility [20].…”
Section: Introductionmentioning
confidence: 99%